(untitled) (Numerus academy review, 2026)
The The language presents researchers and developers of natural language processing (NLP) applications for text and speech grounds that some languages is contrasts with others n lingos phonetically, morphologically, syntactically, and semantically, starting from a discussion the general features of the language, and then specific properties of the language, and the challenge these properties pose to ANLP. This article discusses different challenges of NLP in Arabic and presents some solutions that would guide current and future practitioners in the field of Arabic natural language processing (ANLP)..